Pendampingan Penghitungan Harga Pokok Produksi dan Harga Jual pada UMKM Burger Salsabila - Nainggolan, Yohanna Thresia; Putri, Anindha Zalwana; Lisdawati, Lisdawati; Lailiah, Nurzhahratul; Ananda, Olyvia; Putri, Ferica Christinawati (Universitas Pahlawan Tuanku Tambusai, 2025)
MSMEs play a significant role in Indonesia's economy development, however, many small business owners still struggle with managing their finances, especially in calculating the Cost of Goods Manufactured (COGM) correctly. This community service activity aimed to help the owner of Burger Salsabila, an MSME located in Tarakan City, in calculating COGM. The method used is participatory, involving the business owner in every stage of the activity, from preparation to evaluation. The outcome of the program indicated that previously, the business owner set the selling price of products solely based on market prices without thoroughly calculating the costs incurred during the production process. After receiving training and mentoring, the business owner was able to calculate COGM more comprehensively and accurately. Accurate COGM calculations have provided a better understanding of production cost structures and helped in setting appropriate selling prices to achieve the expected profit.